CONVERSATIONAL IMPLICATURE ANALYSIS OF TEXT MESSAGE BETWEEN NATIVE SPEAKR AND FOREIGN LANGUAGE SPEAKER OF ENGLISH - Anggrarini, Natalia (Universitas Wiralodra, 2017)
In this global era, it is possible to do communication with native speaker of English. Thus, the need to master communicative competence of English communication is needed. Beside face to face communication, people are also need to be able to communicate in different way, such as chat via mobile phone. It is used to call as Short Message Service or SMS. This study is aimed to know the kinds of conversation that happened in their short text message for a month. The classification of conversation is according to the Grice (1975) the formulation of Cooperative Principle in which it is classified into Generalized Conversation Implicature and Particularized Conversational Implicature. The method used in this study is Descriptive Qualitative. It is used to interpret the data according to the conversational classification. The result of this study shows that 81. 25 % the conversations are classified into Generalized Conversational Implicature, and 18. 75% conversations are classified into Particularized Conversational Implicature.